Surface‐enhanced Raman scattering of thiram: Quantitative and theoretical analyses. (15th August 2021) - Oliveira, Marcelo J. S.; Martin, Cibely S.; Rubira, Rafael J. G.; Batagin‐Neto, Augusto; Constantino, Carlos J. L.; Aroca, Ricardo F.
Abstract: The development of strategies to monitor the applications of pesticides is of primary importance. In the present report, two aspects of the surface‐enhanced Raman scattering (SERS) effect of the fungicide thiram were investigated: quantitative analysis using the standard addition method and the thiram adsorption mechanism onto Ag nanostructures using theoretical approach. Experimentally, SERS intensity varies linearly from 1.0 × 10 −8 to 4.0 × 10 −7  mol/L with thiram concentration leading to a limit of detection of 1.2 × 10 −8  mol/L for the band at 560 cm −1 and 1.7 × 10 −9  mol/L for 1386 cm −1 . The loss of linearity (above 10 −6  mol/L) was associated with changes in the Ag colloid aggregation, also indicated by complementary analyses via UV‐Vis extinction spectroscopy, dynamic light scattering, and zeta potential. The differences in the spectral profiles observed for thiram Raman powder and SERS are ascribed to S–S cleavage, leading the degraded thiram adsorbing to Ag surface not only through S atoms but also through methyl groups. Abstract : The analytical detection of distinct analytes at low concentration using surface‐enhanced Raman scattering (SERS) technique has shown to be possible. SERS was successfully applied in the detection and quantification of thiram pesticide in silver colloid.